EFFECT OF NITROGEN SOURCES ON GROWTH, PROTEIN, TOTAL LIPID AMOUNT AND PIGMENT CONTENT IN CHLORELLA VULGARIS - Simsek, Gokce Kendirlioglu; Cetin, A. Kadri (Parlar Scientific Publications (P S P), 2019)
The discovery of valuable metabolites and microalgae containing high lipids has made these organisms economically very important. The aim of this study is to investigate the effects of different nitrogen sources on growth, protein, lipid amount and pigment content of Chlorella vulgaris. The use of ammonium nitrate as a nitrogen source resulted in high concentrations of biomass, protein and lipid while the use of sodium nitrate as a nitrogen source resulted in high concentrations of chlorophyll and astaxanthin. Concentrations of biomass, protein and lipid increased by about 200%, 127.50% and 112.14%, respectively, on day 6 in media where ammonium nitrate was used as a nitrogen source while concentrations of chlorophyll a, chlorophyll b and astaxanthin increased by 45.71%, 192.87% and 118.94%, respectively, on day 6 in media where sodium nitrate was used as a nitrogen source. In conclusion, the amount of lipid and valuable metabolites in Chlorella vulgaris grown in media with appropriate nitrogen sources can be significantly increased.
Keywords: Chlorella vulgaris; Nitrogen sources; Growth; Pigment; Chlorophyll a; Chlorophyll b; Astaxanthin